Recent Advances in Molecular-Imprinting-Based Solid-Phase Extraction of Antibiotics Residues Coupled With Chromatographic Analysis - Sun, Dani; Song, Zhihua; Zhang, Yue; Wang, Yixiao; Lv, Min; Liu, Huitao; Wang, Liyan; Lu, Wenhui; Li, Jinhua; Chen, Lingxin (Frontiers in Environmental Chemistry, 2021)
Abuse and residues of antibiotics cause great harm to organisms and the environment. Appropriate sample pretreatment is usually required for sensitive determination, because of the low content presence of a variety of antibiotics in complicated matrices. Molecular-imprinting-based solid-phase extraction (MISPE) has been widely used for sample pretreatment of antibiotics, using molecularly imprinted polymers (MIPs) as adsorbents. Herein, we comprehensively review the recent advances of MISPE of antibiotics, followed by chromatographic analysis. Various solid-phase extraction (SPE) modes based on MIPs are briefly introduced, such as conventional SPE, dispersive SPE, magnetic SPE, matrix solid-phase dispersion, and pipette-tip SPE. Then, several emerging preparation techniques for antibiotics MIPs are summarized including surface imprinting, nanoimprinting, living/controlled radical polymerization, multitemplate imprinting, multifunctional monomer imprinting, and dummy template imprinting. Subsequently, applications of MISPE to analysis of a variety of antibiotics residues since 2018 are overviewed, including sulfonamides, quinolones, tetracycline, and others. Finally, the preparation and application of antibiotics MIPs are prospected.